Determinants and Consequences of the Use of Digital Finance Platform for Personal Financial Management in Rural China - Wu, Xiao Qian (Curtin University, 2019)
This research aims to investigate the determinants influencing the use of digital finance platform (DFP) for personal financial management (PFM) and its consequences on rural Chinese. Data are collected from 403 rural residents in China and analysed using Partial Least Squares-Structural Equation Modeling. The findings show that performance expectancy, effort expectancy and facilitating conditions positively influence the use of DFP, which then lead to net benefits and user satisfaction on PFM of rural Chinese.